Pemanfaatan Penggunaan Media Sosial Sebagai Sarana Edukasi Di Kalangan Pelajar - Nugroho, Agus Susilo; Ariyanto, Arif Setia Sandi; Muryanto, Muhammad (Jurnal Arba - Multidisiplin Pengabdian Masyarakat, 2024)
This article discusses using social media as a means of education among students. In this service activity, a survey was conducted to determine students' social media usage habits, followed by a workshop that provided an understanding of digital literacy and techniques for using social media for learning. The results show an increase in students' understanding of using social media as an educational tool after attending the workshop. However, the challenge of distinguishing between valid information and the temptation of entertainment content remains. The conclusion states that social media has great potential to support education if used correctly. Suggestions are given for schools, teachers, and parents to be more active in guiding and supervising students' use of social media and integrating digital literacy into the learning curriculum.